2015
DOI: 10.1063/1.4930128
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal ion-temperature-gradient driven vortices in an inhomogeneous magnetoplasma with non-Maxwellian electrons

Abstract: Nonlinear equations which govern the dynamics of low-frequency toroidal ion-temperature-gradient driven modes (i.e., ω≪ωci, where ωci is the ion gyro-frequency) are derived in the presence of equilibrium density, temperature, and magnetic field gradients. In the nonlinear case, solutions in the form of dipolar vortices and vortex street are presented for a plasma comprising of Maxwellian ions and nonthermal electrons that are embedded in an external magnetic field. By using Braginskii's transport equations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Here, 𝜈 in is defined as the frequency of ion-neutral collision. Using the Equation ( 21) in (25), we arrive at following (1 + 1) dimensional nonlinear partial differential equation for the dissipative case…”
Section: Dissipative Casementioning
confidence: 99%
See 1 more Smart Citation
“…Here, 𝜈 in is defined as the frequency of ion-neutral collision. Using the Equation ( 21) in (25), we arrive at following (1 + 1) dimensional nonlinear partial differential equation for the dissipative case…”
Section: Dissipative Casementioning
confidence: 99%
“…[24] Mirza et al studied the formation of nonlinear vortex structures in ITG mode in the presence of magnetic shear and suprathermal electrons. [25] They found that presence of hotter electrons in the system modify the scale length of vortex structures. Recently, Hassan et al [26] studied the effect of nonthermal electrons on the formation of solitons and shock in ITG-driven drift acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…and U=u− V 0 η represents the Doppler shifted velocity. In equation ( 16) by expressing ∂ ξ j=D ξ j since (∂ x j∂ ξ −∂ ξ j∂ x )j=0, we can express equation (16) as…”
Section: Stationary Solutions For Counter Rotating Vorticesmentioning
confidence: 99%
“…The investigation of nonlinear behavior of drift waves in a spatially inhomogeneous magnetoplasma leads to the development of structures like solitons, shocks and vortices. Many research papers have been dedicated to explore the formation of these structures and the study of their properties in ordinary electronion (e-i) [6,[10][11][12][13][14][15][16][17][18] and dusty plasmas [19].…”
Section: Introductionmentioning
confidence: 99%
“…23 Important problems such as cyclotron heating and wave resonance with runaway (or superthermal) electrons have been considered by this approach. 24,25 Finally, it has been also observed that in a dusty plasma, the excess of superthermal plasma particles affects not only the wave-resonance characteristics (dispersion relations and damping/growth rates), but alters the resulting electrical charge of the dust particles as well. [26][27][28][29][30][31] Some theories have been proposed to address the origin of κVDFs from a fundamental set of postulates.…”
Section: Introductionmentioning
confidence: 99%